A CORPUS-BASED ANALYSIS ON MULTILINGUAL CHILDREN'S NARRATIVES IN INDONESIAN CONTEXTS - Laily Zen, Evynurul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
Children’s narratives have served as an effective diagnostic tool for teachers and researchers to engage to a variety of language acquisition and development aspects. Previous works have extensively assessed this type of language production along two dimensions; story memory and story quality in which the first concerns on children’s ability to accurately reproduce units of information within the story, while the second emphasizes their understanding of story structures. Our analysis focuses on the second where we carefully look at two categories; orientations (person, time, place, connectors, etc) and evaluation (personal judgment). Our data were based in part on a limited corpus of multilingual written production of 261 third graders in 6 primary schools in east java, Indonesia. This dataset contained the production of both personal narratives in which our participants had to write their personally experienced event of school holiday and fictional narratives where they had to rewrite a short video story of a perfect father’s day. To generate the targeted expressions from our relatively large datasets, we utilized a corpus tool of AntConc. Our analysis has echoed several findings. In terms of ‘person’ orientation, our participants were consistent in orienting their personal narratives with ‘I’ and their fictional narratives with ‘dad/father’. The emergence of the word ‘home’ in the first place was particularly interesting as a key to explain ‘place’ orientation that it translates a place to start and end the activities in children’s point of view. The word ‘after’ and ‘then’ to connect events were heavily found in our data that it illustrates the pedagogical need to enrich their lexical knowledge. Finally, at the expense of being multilingual, evidence of code-mixing was also apparent in our participants’ English narratives that this may posit pedagogical implication too.